A note on stability and fractal dimension of bivariate α-fractal functions - Agrawal V.; Som T.; Verma S. (My University, 2025)
We study the continuous dependence of the so-called (bivariate) α-fractal function on the parameters such as the scaling function α, net △ of rectangular grid, and the base function s involved in its construction. Furthermore, we establish some results regarding its dimension. © 2023, The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.